Dragon in the Tropics : Hugo Chavez and the Political Economy of Revolution in Venezuela - Corrales, Javier, 1966- (Book collections on Project MUSE., 2011)
"A study of the Venezuelan revolution headed by Hugo Chávez, first elected president in 1999, with emphasis on how Chávez took a frail but still pluralistic democracy and turned it into a semi-authoritarian regime, achieving political transformation at great cost to the country's institutions, including its oil industry"--Provided by publisher.